PENGARUH MEDIA TIGA DIMENSI PADA PEMBELAJARAN GEOGRAFI TERHADAP HASIL BELAJAR SISWA SMAN 8 PONTIANAK - Egira Wahyuni; Maria Ulfah; L.M Hari C (Universitas Tanjungpura, 2020)
Abstract The study aimed to find out how the use of three-dimensional learning media on geography studies affects the study of X IPS SMAN 8 Pontianak. The method of research used is experiment with a quantitative research approach. The source of data for this study is an X IPS SMAN 8 Pontianak and the data will result from student’s study on the X IPS SMAN 8 Pontianak. Research shows the average result of learning from students who use two-dimensional learning media on geography at 67,69 and an average of studying students who use three-dimensional learning media by 87,39. Then it may be concluded that there is a significant difference between the average result of student’s learning media using three-dimensional learning media and the average of student’s learning media that uses two-dimensional learning media that is a proven by a value of 8,438 and a table with a margin of 1,698. Furthermore, the use of three-dimensional learning media on geography can affect student’s learning by an effect-effect of 0,78. Keywords: Geography Studies, Learning Result, Three-Dimensional Media.